INDICATORS OF HEART RATE VARIABILITY IN HEALTHY VOLUNTEERS DEPENDING ON THE RESPIRATION RATE AND INHALATION-EXHALATION RATIO - Kulik, A.L.; Zaderihin, A.K.; Shulgin, V.I.; Martynenko, A.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
At the 4 healthy volunteers aged 22 to 29 years (2 men and 2 women) with a body mass index from 21 to 23 individual characteristics and general laws of the reactions of the spectral indices of HRV in the low and high frequencies of breathing with different ratios of breaths were examined. It is shown that the spectrum of HRV LF maximum is reached at a frequency of 6 breaths per minute. A maximum of HF range of HRV recorded during breathing with a frequency of 10-12 per minute. Demonstrated that in addition to the frequency of paced breathing the inhalation-exhalation ratio significantly affects the power and structure of the spectrum of HRV. Maximum values of the TR spectrum of HRV and LF HRV spectrum lie in the range of 1/1, 2-1/1,3, and the maximum HP of the spectrum of HRV – in the range of 1/1,3-1/1,4. Using the best balance of inhalation-exhalation allow more subtly to influence the regulatory process.